Social innovations in outsourcing: an empirical investigation of impact sourcing companies in India - M.S. Sandeep; M.N. Ravishankar (2015)
Impact sourcing – the practice of bringing digitally-enabled outsourcing jobs to marginalized individuals – is an important emerging social innovation in the outsourcing industry. The impact sourcing model of delivering Information Technology and Business Process Outsourcing (IT–BPO) services not only seeks to deliver business value for clients, but is also driven by an explicit social mission to help marginalized communities enjoy the benefits of globalization. This dual focus has led to the ambitious claim that social value creation can be integral to (and not always by-products of) innovative IT–BPO models. Given the relative newness of the impact sourcing business model there is scarce research about how impact sourcing companies emerge and the process through which entrepreneurs build and operate such companies. This paper draws on a qualitative study of seven Indian impact sourcing companies and develops a process model of the individual-level motivational triggers of impact sourcing entrepreneurship, the entrepreneurial actions underpinning different phases of venture creation and the positive institutional-level influences on impact sourcing. The paper argues that since deeply personalized values are central to the creation and development of impact sourcing companies, the business model may not be easy to replicate. The analysis highlights an intensive period of embedding and robust alliances with local partners as crucial for the scalability and sustainability of the impact sourcing business model. It also emphasizes the role of ‘social’ encoding and mimicry in determining the extent to which impact sourcing companies are able to retain their commitment to marginalized communities.